Psychopathology and Parenting Practices of Parents of Preschool Children with Behavior Problems - Harvey, Elizabeth (2011)
OBJECTIVE: This study investigated associations among different types of parental psychopathology and several specific parenting practices. DESIGN: Mothers (n = 182) and fathers (n = 126) of preschool-aged children with behavior problems completed questionnaires assessing parental psychopathology and parenting practices, and participated in observed parent-child interactions. RESULTS: Maternal depression, anxiety, substance abuse, and several different personality disorder traits were related to maternal negativity, laxness, and lack of warmth. Paranoid, schizoid, schizotypal, and borderline personality disorder symptoms predicted mothers’ parenting practices, even when statistically controlling for other types of psychopathology. For fathers, those same symptoms, dependent and avoidant symptoms, and substance abuse symptoms were associated with self-reported lax parenting. Evidence emerged that psychopathology in one parent was associated with less overreactivity in the other parent. CONCLUSIONS: Many aspects of parents’ psychological functioning play a role in determining specific parenting practices, including personality disorder symptoms.